A study of collaborative knowledge construction in stem via educational robotics - Socratous, Chrysanthos; Ioannou, Andri (My University, 2018)
The educational robotics learning environment can integrate the benefits of robotics technology, computer supported collaborative learning (CSCL) and problem-based pedagogy, in an authentic learning space, simulating real-world problems. This study investigated primary school students’ patterns of knowledge construction in STEM, as they engaged in collaborative problem-solving using educational robotics. Data analysis involved micro-level examination of students’ discourse and interactions with their peers, the teacher and the robot, and students’ delivered solutions (software programs and worksheets). The study presents three conditions that appear to relate to higher levels of knowledge construction: (i) embodied interaction with the robot; (ii) fair contribution by teammates adhering to predefined roles, and (iii) cognitive dissonance as a result of the robot’s failure to perform the expected outcome. The study contributes to the design of educational robotics learning environments and conditions for collaborative knowledge construction in the STEM field.
Keywords: Computer aided instruction; Educational robots; Knowledge management; E-learning